Analysis of Risk Factors for Chronic Kidney Failure - Nunuk Sudarmiyati; Irfansyah Baharuddin Pakki; Iwan Muhamad Ramdan (GLOBAL HEALTH SCIENCE GROUP, 2025)
The background of this study focused on the increasing incidence of chronic renal failure at Kudungga Sangatta Hospital, East Kutai Regency, which is a serious concern in an effort to improve the quality of public health services. The general objective was to analyze the risk factors of chronic renal failure in Kudungga Sangatta Hospital, East Kutai Regency. This type of research is an analytic observational research with case control design or case control study. The non-random sampling method is purposive sampling as many as 140 people, as for data collection techniques, namely, the preparation stage (preparing a research permit, and conducting a preliminary study), after that there is an implementation stage (collecting respondent data, sorting samples according to sample criteria in two sample groups, filling out questionnaire data, and collecting research instruments). The data analysis techniques in the study were editing, coding, shorting, data entry, and data cleaning. Age was significantly associated with the incidence of acute renal failure (P < 0.001). Family history of hypertension is significantly associated with the incidence of acute renal failure (P < 0.001, OR = 69.750). Family history of diabetes mellitus was not significantly associated with the incidence of acute renal failure (P = 0.806). Taking Analgesic and NSAID drugs were not significantly associated with the incidence of acute renal failure (P > 0.05). The conclusion is that there is a relationship between age and family history of hypertension with the incidence of chronic renal failure and there is no relationship between family history of diabetes mellitus, and using analgesic drugs and NSAIDs is not significantly related to the incidence of acute renal failure at Kudungga Sangatta Hospital, East Kutai Regency.